HD 161701, a chemically peculiar binary with a HgMn primary and an Ap secondary - Gonzalez, Jorge Federico (2013)
In recent years, HgMn stars have attracted attention after in several of them surface chemical spots of different elements were discovered, whose origin and possible connection with binarity and magnetic fields is not clear yet. Aims. We perform a complete study of the HgMn binary HD 161701, including the determination of physical parameters and photospheric chemical abundances.